MircroRNA Let-7a-5p in Airway Smooth Muscle Cells is Most Responsive to High Stretch in Association With Cell Mechanics Modulation - Wen, Kang; Ni, Kai; Guo, Jia; Bu, Bing; Liu, Lei; Pan, Yan; Li, Jingjing; Luo, Mingzhi; Deng, Linhong (Frontiers in Physiology, 2022)
Objective: Mechanical ventilation (MV) has been reported to decrease lung compliance and thus cause ventilator-induced lung injury (VILI), but their underlying mechanisms are not fully understood. Here, we hypothesize that the high stretch imposed by MV on bronchial airways may stimulate airway smooth muscle cells (ASMCs) to modulate the specific miRNA(s) that may in turn modulate the cell mechanics so that to decrease lung compliance. This study was aimed to test this hypothesis by identifying miRNA that is most responsive to high stretch, and subsequently investigated the effects of the miRNA on mechanical behaviors of ASMCs. Methods: miRNAs related to inflammatory airway diseases were obtained via bioinformatics data mining, and then tested with cultured ASMCs for their expression variations in response to high stretch (13%, 0.5 Hz) simulating in vivo MV-imposed strain on airways. Subsequently, we transfected cultured ASMCs with mimics and inhibitor of the miRNA that is most responsive to high stretch, followed by evaluation of morphology, stiffness, traction force, and mRNA expression of cytoskeleton/focal adhesion related molecules. Results: 29 miRNAs were identified to be related to inflammatory airway diseases, among which let-7a-5p was the most responsive to high stretch. Transfection of cultured ASMCs with let-7a-5p mimics or inhibitor led to increase or decrease in aspect ratio, stiffness, traction force, migration, stress fiber distribution, mRNA expression of smooth muscle alpha actin (SMA), myosin light chain kinase (MLCK), some subfamily members of integrin (Itg) and talin. Direct binding between let-7a-5p and ItgαV was also detected. Conclusion: We demonstrated that high stretch indeed enhanced the expression of let-7a-5p in ASMCs, which in turn led to changes in morphology and mechanical behaviors together with modulation of molecules associated with cytoskeletal structure and focal adhesion of ASMCs. These changes of ASMCs such as increased stiffness and traction force may largely contribute to lung compliance reduction that is known to be involved in VILI. Thus these findings provide not only an alternative mechanism for the pathogenesis of VILI, but also a scientific basis for targeting miRNAs such as let-7a-5p for early diagnosis and therapeutic improvement of lung compliance in prevention and treatment of VILI.